Effect of Acupressure Techniques and Endorphin Massage on Back Pain Intensity in Third-Trimester Pregnant Women - Ulya, Rahmatul; Panduragan, Santhna Letchmi; Radhia, Mekar Zenni; Zaini S, Hanifa (International Journal of Multidisciplinary Approach Research and Science, 2025)
Back pain in pregnancy is common, especially in the third trimester of pregnancy. In the world of health, alternative methods are being created to reduce pain in mothers during pregnancy and childbirth. Endorphin massage is the best nonpharmacological therapy to deal with these problems. This study aimed to determine the effect of acupressure and endorphin massage techniques on the intensity of back pain in third-trimester pregnant women. This type of research is a pre-experiment with one group pre-test post-test design. Samples were taken from a population that met the inclusion criteria of 20 pregnant women. The sampling technique used an accidental sampling technique. The research instrument used the SOP of acupressure and endorphin massage techniques and the Numeric Rating Scale pain observation sheet. The results showed that before acupressure and endorphin massage, almost half (45%) of all pregnant women experienced severe pain. After acupressure and endorphine massage, none of the respondents (0%) experienced severe pain. The results of the Dependent T-test with α = 0.05 obtained Asymp.Sig.=0.001, so the p-value <0.05 indicates the effect of acupressure and endorphin massage techniques on the intensity of back pain in pregnant women. The conclusion is that there is an effect of acupressure techniques and endorphin massage on the intensity of back pain in third-trimester pregnant women. It is recommended that health workers improve their competence in the service of acupressure techniques and endorphine massage.